Relapsing Polychondritis - Beata Sosada; Katarzyna Loza; Ewelina Bialo-Wojcicka (Case Reports in Dermatological Medicine)
Relapsing polychondritis (RP) is a rare systemic disease characterized by recurrent, widespread chondritis of the auricular, nasal, and tracheal cartilages. Additional clinical features include audiovestibular dysfunction, ocular inflammation, vasculitis, myocarditis, and nonerosive arthritis. Although the cause remains unknown, the etiology is suspected to be autoimmune. We describe a case of a 31-year-old woman with a four-month history of bilateral auricular and nasal chondritis. Infectious and neoplastic diseases were excluded by imaging and laboratory examinations. RP was diagnosed based on three McAdam’s criteria. The patient was medicated with oral prednisolone and methotrexate with positive clinical response. In this case clinical history and detailed physical examination were fundamental in concluding the correct diagnosis and administrating the appropriate medication.